Peran Eudaimonic Well Being sebagai Mediasi Pengaruh Perilaku Kepemimpinan terhadap Kinerja Organisasi UMKM - MFitri Chairunnisa; Dian Mala Fithriani Aira; Ade Perdana Siregar (Universitas Batanghari, 2022)
Business organizations in MSMEs are oriented towards profit achievement and can contribute to the economy. Efforts in achieving the goals of MSMEs should be organizational leaders who can empower the potential of each employee. The role of the leader can create a comfortable environment that can encourage increased employee performance, one of the factors is the happiness felt from employees when carrying out work in the organization. The aims of this study are (1) to analyze the influence of leadership behavior on the organizational performance of MSMEs; (2) analyze the influence of leadership behavior on eudaimonic well being; (3) analyzing the effect of eudaimonic well being on the organizational performance of MSMEs; (4) analyzing the role of eudaimonic well being in mediating the influence of leadership behavior on the organizational performance of SMEs. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The results of the study are (1) leadership behavior shows a significant positive influence on the organizational performance of SMEs; (2) leadership behavior shows a significant positive effect on eudaimonic well being; (3) eudaimonic well being shows a significant positive effect on the organizational performance of SMEs; (4) eudaimonic well being as a mediation of the influence of leadership behavior shows a significant positive influence on the organizational performance of SMEs